COACHING AS THE PEDAGOGICAL TECHNOLOGY FOR TRAINING FUTURE SPECIALISTS - Nazarmatova Yorqinoy (Bright Mind Publishing, 2025)
This article deals with the application of coaching technology in the educational process and its significance in the formation of professional competencies. The research results show that innovative pedagogical technologies, in particular, the coaching approach, are a helpful tool for increasing the activity of the student learning process, strengthening their motivation, developing logical thinking and leadership abilities.
Keywords: Coach; coaching; coaching technology, educational coaching.